The Hydra Nature of Book Banning and Censorship - Michelle Boyd Waters; Shelly K. Unsicker-Durham (University of Oklahoma Libraries, 2023)
In Fall of 2022 two researchers set out to explore both scholarly work on censorship and news articles via social media, to help gain a broader understanding of censorship and book banning trends. The following research question guided their research: What does this wave of book banning and censorship look like across the US? What they discovered is a kind of censorship-Hydra, an evolving beast posing an ever-present danger, one that will likely take the courage, collaboration, and ingenuity of educators everywhere. This article offers a snapshot of this current beast of book banning and censorship in the form of two annotated bibliographies-one focused on news reports and trends in social media-the other focused on academic searches of scholarly articles.